Development of Discovery Learning Model Using Scientific Approach to Increase Student’s Comprehension and Communication Skills (Universitas Negeri Semarang, 2018)
To day National curriculum submit to the basic oppinion that the knowlege can’t translet just at the momment from the teacher to the stuent. It’s because the students are the subject who have ability to active loding for, processing, constructing and using the knowledge, so that learning that have facilities of the teacher, the teacher need to giving opportunity to the students for constructing the knowledgein kognitive process. The ones that influential in learning process is act of determining from learning models by the teacher . Learning models that can be using is discovery learning. The purpose of this riset to know the characteristic learning models discovery learning, to know the comunicative skills that develop and to know the efectively learning models discovery learning to increase science concept capability. Design of study is research and development are described in step follows: 1) preliminary studies, 2) initial product development, 3) product trial to a small group, 4) field product trials, 5) product revision, 6) Final product have been revision. Results from the research show that: 1) The characteristic Discovery Learning Model can looked of learning syntax which of ; stimulation, problem statement, data collecting, data processing, verification, and generalization. 2) Discovery Learning Model emphasizes the discovery of a concepts whose problems are engineered by the teacher. 3) Result obtained using t – test on pre-test and post – test is significant visible from the calculation t is on 8.889 while t table 2.028. This shows t count is greater than t table. 4) The development of communication skills of students has increased this is indicated from discovery I 33% and discovery II 75%. Written communication skills of the highest on the indicator of translation of goals and the lowest on the indicator material mastery. Based on the results can be concluded that: development of Discovery Learning Model should be based sintax of discovery learning, development of Discovery Learning Model using scienstific can be increase student’s comprehension and communication skills.